Retrospective study examining complications and iatrogenic pseudopregnancy in bitches neutered in different stages of the oestrous cycle: identification of an ‘early neutering window’ in bitches - Moxon, Rachel; England, Gary C. W. (Frontiers in Veterinary Science, 2026)
IntroductionNeutering in the anoestrus period is most commonly recommended for bitches due to reduced risk of intraoperative bleeding and iatrogenic pseudopregnancy. However, there is a possible second period for neutering, commencing after oestrus until the time when prolactin concentrations increase.MethodsThis retrospective study compared reports of intraoperative bleeding (categorised in two ways: excluding and including bleeds from the skin and subcutaneous tissue/fat) and cases of pseudopregnancy between bitches neutered during an ‘early’ period (EP bitches, neutered from the end of oestrus until day 43 after ovulation, n = 319), during a ‘conventional’ period (CP bitches, neutered 90 or more days from estimated ovulation date, n = 1,993) and bitches neutered in an ‘at greatest risk’ period (GRP bitches, neutered between 44 and 89 days from estimated ovulation date, n = 231). Data for pseudopregnancy post-neutering were gathered using two methods (1) clinical indicators from electronic health records and (2) routinely collected behavioural data for behaviours that have been associated with pseudopregnancy.ResultsThere was no association between neuter period and the presence of an intraoperative bleed, either when excluding or including bleeding from the skin and subcutaneous tissue/fat (3.8–4.4% EP, 5.8–8.8% CP, and 7.4–11.3% GRP bitches). Only six cases of pseudopregnancy after neutering were identified in clinical records: two EP bitches (0.6%), one CP bitch (0.05%) and three GRP bitches (1.3%); associations were not evaluated statistically due to the small number of cases. Examinations of behavioural data found no association between neuter period and trait scores for ‘General Anxiety’, ‘Body Sensitivity’ and ‘Separation-related behaviours’ from dog behaviour questionnaires. However, EP (4.1%) and CP bitches (11.7%) had reduced odds of having a behaviour incident and/or development plan related to fear or anxiety and/or aggression post-neutering compared to GRP bitches (20.8%).ConclusionThe results suggest that neutering bitches during the ‘early’ period may be a suitable alternative to the ‘conventional’ period. Additionally, the results support the generally well-accepted advice to avoid neutering bitches during the period of greatest risk.